Anti-PEG IgM Response against PEGylated Liposomes in Mice and Rats - Hiroshi Kiwada; Tatsuhiro Ishida; Yumi Uehara; Yuki Hashiguchi; Ami Imoto; Taro Shimizu; Masako Ichihara (MDPI AG, 2010)
We have reported that PEGylated liposomes lose their long-circulating properties when they are administered repeatedly at certain intervals to the same animal. This unexpected phenomenon is referred to as the accelerated blood clearance (ABC) phenomenon. We recently showed that the ABC phenomenon is triggered via the abundant secretion of anti-PEG IgM in response to the first dose of PEGylated liposomes. However, the details of the underlying mechanism for the induction of anti-PEG IgM production are yet to be elucidated. The present study demonstrated that the spleen is a major organ involved in the secretion of anti-PEG IgM in mice and rats. Anti-PEG IgM production was detected in nude, T-cell deficient mice, but not in SCID mice with B- and T-cell deficiencies. These observations indicate that splenic B-cells secret anti-PEG IgM without help from T-cells. Sequential injections of PEGylated liposomes into the same mice did not promote isotype switching from IgM to IgG. Accordingly, PEGylated liposomes may function as a type-2, T-cell-independent antigen (TI-2 antigen) during anti-PEG IgM production. Although the underlying mechanism that causes an anti-PEG IgM response against PEGylated liposomes is not yet clear, our findings give implications in revealing the anti-PEG IgM response against PEGylated liposome.